2012
DOI: 10.1112/blms/bds057
|View full text |Cite
|
Sign up to set email alerts
|

Vaisman metrics on solvmanifolds and Oeljeklaus-Toma manifolds

Abstract: We prove the non‐existence of Vaisman metrics on some solvmanifolds with left‐invariant complex structures. By this theorem, we show that Oeljeklaus–Toma manifolds do not admit Vaisman metrics.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 26 publications
0
57
0
Order By: Relevance
“…By a straightforward computation that results from (4.10) being an equality, we also have the following: Remark 4.9. In [Kas13] it is shown that any OT manifold X admits a solvmanifold presentation Γ \ G, in such a way that the natural complex structure on G is G-left invariant. It is well known that the Lie algebra cohomology H * (g) injects into H * dR (X).…”
Section: Preliminary Facts On Cousin Groupsmentioning
confidence: 99%
“…By a straightforward computation that results from (4.10) being an equality, we also have the following: Remark 4.9. In [Kas13] it is shown that any OT manifold X admits a solvmanifold presentation Γ \ G, in such a way that the natural complex structure on G is G-left invariant. It is well known that the Lie algebra cohomology H * (g) injects into H * dR (X).…”
Section: Preliminary Facts On Cousin Groupsmentioning
confidence: 99%
“…• Kasuya proved in [56] that OT manifolds do not admit any Vaisman metric, by studying the Morse-Novikov cohomology H * θ of solvmanifolds Γ\G equipped with LCS structures, where θ denotes the corresponding Lee form of the LCS structure. • Ornea and Verbitsky proved in [76] that OT manifolds of type (s, 1) contain no nontrivial complex submanifolds.…”
Section: Oeljeklaus-toma Manifoldsmentioning
confidence: 99%
“…[14]). Kasuya [7] showed that OT-manifolds are in fact solvmanifolds, and proved that OT-manifold of type (s, 1) has no Vaisman structures. We see that the solvmanifold Γ∖G is OT-manifold of type (2,1).…”
Section: Main Theorem the Solvable Lie Group G Admits A Lattice γmentioning
confidence: 99%
“…[7] Let g be the solvable Lie algebra of G. Then g * has a basis {λ i , µ i , υ,ῡ} such that [15] proved that the first Betti number of a Vaisman manifold is odd. Thus, the solvmanifold Γ∖G has a LCK structure, but it has no Vaisman structures.…”
Section: Proof Of Main Theoremmentioning
confidence: 99%